LOVE YOURSELF, LOVE OTHERS: MENGAJARKAN SISWA SD MENGHARGAI DIRI SENDIRI DAN SESAMA - Claudes, Juniven; , Nivia; Utomo, Mochamad Hammam Tegar; Oktariana, Putri; Saputro, Bayu Eko; Setiawan, Dany; Dewi, Fransisca Iriani R. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
School is a place where children learn and develop themselves. Children studying in primary school are developing their character and social skills through interaction with the wider social environment. Therefore, the school social environment is quite crucial. Bullying and self-harm among elementary school students are serious problems that can have a negative impact on children's mental and emotional development. At SDN P, bullying behavior was found among students in grades 4 to 6, as well as several cases of self-harm among students in grades 5 and 6. This has a negative impact on the well-being of students at school. Therefore, a psychoeducational activity entitled